The influence of impact-based severe weather warnings on risk perceptions and intended protective actions - Potter, Sally H.; Kreft, Peter V.; Milojev, Petar; Noble, Chris; Montz, Burrell; Dhellemmes, Amandine; Woods, Richard J.; Gauden-Ing, Sarah (My University, 2018)
This paper presents the results of an online survey of the New Zealand public (n = 1364), conducted in 2015, that tested the influence of impact-based severe weather warnings on risk perceptions and intended protective actions. We used a hypothetical severe weather event involving strong winds, with 50% of participants receiving an impact-based warning, and 50% receiving a more traditional phenomenon-based warning (which in this case is when the wind speed is expected to be higher than a given number). Our results indicate that impact-based warnings may be more effective than phenomenon-based warnings in influencing the recipient's perception of the hazardous event (their sense of threat, concern, and understanding of the potential impacts), but this does not translate to a higher level of action. Characteristics of gender, age, and location of residence were also influences on risk perceptions and intended actions. However, experience with having been affected by strong winds in the past was not a strong influence on intending to respond. Our findings support the inclusion of information about hazards, impacts, and ‘what to do’ information in a warning message.